John's gospel - Stibbe, Mark W. G. (Routledge, 1994)
An innovative study showing how literary methodologies such as structuralism, narrative criticism and deconstructionism can be used to illuminate biblical texts. A detailed introduction makes it accessible to the non-specialist.
Keywords: Bible. -- John -- Criticism, interpretation, etc.; Bible. -- John; Bibel -- Johannesevangelium; Bible as literature.; Bible (Littérature); RELIGION -- Biblical Studies -- New Testament.; RELIGION -- Biblical Studies -- Jesus, the Gospels & Acts.; Bible as literature; Johannes (bijbelboek); Christianity -- Scriptures; Electronic books.; Criticism, interpretation, etc.